2017
DOI: 10.1016/j.jbiomech.2017.06.046
|View full text |Cite
|
Sign up to set email alerts
|

On estimating intraventricular hemodynamic forces from endocardial dynamics: A comparative study with 4D flow MRI

Abstract: Intraventricular pressure gradients or hemodynamic forces, which are their global measure integrated over the left ventricular volume, have a fundamental importance in ventricular function. They may help revealing a sub-optimal cardiac function that is not evident in terms of tissue motion, which is naturally heterogeneous and variable, and can influence cardiac adaptation. However, hemodynamic forces are not utilized in clinical cardiology due to the unavailability of simple non-invasive measurement tools. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 31 publications
1
74
1
Order By: Relevance
“…Such pathological rise in the in-plane KE may exert heterogenous haemodynamic forces on the LV wall, possibly contributing to more dilatation and increase in endothelial dysfunction in the endocardium [3740]. …”
Section: Discussionmentioning
confidence: 99%
“…Such pathological rise in the in-plane KE may exert heterogenous haemodynamic forces on the LV wall, possibly contributing to more dilatation and increase in endothelial dysfunction in the endocardium [3740]. …”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is explained by the persistence of the ascending segment contraction during the isovolumic diastolic phase. (16)(17)(18)(19)(20)(21)(22) We have found that the endocardium is completely depolarized during the rst part of the QRS. If according to our studies the depolarization of the ascending segment starts 25.8 ms on average after that of the descending segment and its contraction persists for the same period of time, the condition of ventricular contraction will last approximately 400 ms. On the other hand, as ventricular systole lasts about 300 ms, the remaining 100 ms correspond to the diastolic isovolumic phase (erroneously called isovolumic relaxation, because as we see there is ventricular contraction).…”
Section: Resultsmentioning
confidence: 99%
“…A validation study compared flow forces computed by 4D Flow MRI with the same obtained from a mathematical model that uses endocardial motion on three apical projections and the size of the aortic and mitral orifice demonstrating the accuracy of the model. Therefore, the knowledge of the LV endocardial motion from ST echocardiography, as it is commonly used to evaluate myocardial strain, also allow estimations of flow forces [ 27 ].…”
Section: Lines Of Research In Literaturementioning
confidence: 99%
“…The same ST data are then used to evaluate the hemodynamic forces associated with blood flow. A previous study [ 27 ] demonstrated that flow forces (which is a synonymous for “hemodynamic forces”, “flow momentum” or “average IVPGs” also used in literature) can be estimated from the knowledge of the LV geometry and endocardial velocities, obtained by ST, plus the area of the aortic and mitral orifices. The complete mathematical details of the method for transforming endocardial dynamics into flow forces are reported elsewhere [ 27 ] and the concept is only quickly summarized here.…”
Section: Exemplary Clinical Casesmentioning
confidence: 99%